Կրոնաեկեղեցական բառաշերտը Միսաք Մեծարենցի ստեղծագործության մեջ - Առաքելյան, Կ. (ՀՀ ԳԱԱ հրատ.)
In the works of Missak Metsarents, words belonging to the religious-ecclesiastic vocabulary have a special stylistic role in the process of poetic image creation. The use of these lexical units, endows his poetry with a special kind of lyricism and psychologism, enhancing the philosophical motifs of his worksВ творчестве Мисака Мецаренца религиозно-церковная лексика играет особую стилистическую роль при создании поэтического образа. Обращение к данной лексике придает его поэзии особый лиризм и психологизм, усиливая философские мотивы его творчества.
Keywords: Գրականություն